The Influence of Exchange Rate on CPO Exports of Indonesia - Agung Prasetyo; Sri Marwanti; Darsono . (Muhammadiyah University Press, 2017)
This study analyzes the effect of the exchange rate (IDR to US Dollar) on Indonesian CPO exports using Error Correction Model (ECM). The result of ECM analysis showed that exchange rate has a weak effect on Indonesian CPO export. These were due to several things; first, it takes a time to produce CPO. Second, importers are unaware of price changes. Third, policy factors, such as refusal of Indonesian CPO in USA and imposition of high import duty tariff in France. Fourth, price factor of CPO substitution goods and negative issues in the palm oil industry. Fifth, Indonesian exporters were less creative in marketing CPO products than Malaysia. ECM analysis also resulted that CPO production and CPO prices have no effect on Indonesian CPO exports, while the price of soybean oil and CPO production in the previous month has a strong influence on Indonesian CPO exports. Indonesian CPO export is inelastic.